Identification of the Flavonoid Luteolin as a Repressor of the Transcription Factor Hepatocyte Nuclear Factor 4α - Li, Juan (J Biol Chem, 2015)
Hepatocyte nuclear factor 4α (HNF4α) is a nuclear receptor that regulates the expression of genes involved in the secretion of apolipoprotein B (apoB)-containing lipoproteins and in glucose metabolism. In the present study, we identified a naturally occurring flavonoid, luteolin, as a repressor of HNF4α by screening for effectors of the human microsomal triglyceride transfer protein (MTP) promoter. Luciferase reporter gene assays revealed that the activity of the MTP gene promoter was suppressed by luteolin and that the mutation of HNF4α-binding element abolished luteolin responsiveness. Luteolin treatment caused a significant decrease in the mRNA levels of HNF4α target genes in HepG2 cells and inhibited apoB-containing lipoprotein secretion in HepG2 and differentiated Caco2 cells. The interaction between luteolin and HNF4α was demonstrated using absorption spectrum analysis and luteolin-immobilized beads. Luteolin did not affect the DNA binding of HNF4α to the promoter region of its target genes but suppressed the acetylation level of histone H3 in the promoter region of certain HNF4α target genes. Short term treatment of mice with luteolin significantly suppressed the expression of HNF4α target genes in the liver. In addition, long term treatment of mice with luteolin significantly suppressed their diet-induced obesity and improved their serum glucose and lipid parameters. Importantly, long term luteolin treatment lowered serum VLDL and LDL cholesterol and serum apoB protein levels, which was not accompanied by fat accumulation in the liver. These results suggest that the flavonoid luteolin ameliorates an atherogenic lipid profile in vivo that is likely to be mediated through the inactivation of HNF4α.